The Development of Graphic Design with the Content of Literary Literacyto Improve the Local Economy in the Convection Business Group in Sumbersari Village Bondowoso Regency - Akhmad Taufiq; Fitri Nura Murti; Siswanto Siswanto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
This article describes a graphic design development program with the content of literary literacy in Sumbersari, Maesan, and Bondowoso villages. This activity was the second year agenda with the vision of creating a literacy-based convection village. This year, the team collaborated with the youth community of Sumbersari village, namely “Pusaka” (Pemuda Sumbersari Krajan) which consisted of 32 youngsters to develop the potential of the village in the convection field. The human resources in Krajan, Sumbersari were 13 tailors, 1 hijab convection, and 3 screen printing micro business. So far, these businesses were still traditional-domestic. Through target needs analysis, the business groups required product and business branding in order to compete in a wider market and increase their income. The team focused on collecting data and recruiting human resources by program socialization, product branding and additional graphic design skills training that aimed at increasing value and building product character, as well as capacity building in market services. The program was relatively successful because an industrial bag based on screen printing skills has been formed which was initiated by the team named “Pusaka Connection”. Pusaka Connection was the center for business production and marketing with the brand named